Prosedur Pembayaran Payment Request Melalui Sarana Centra di PT Pelindo Multi Terminal (Studi Kasus: PT. Pelindo Multi Terminal) - Marwah Khairunnisa Siregar (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Payment System is a system related to the transfer of a sum of money from one party to another. Company payment systems that we often encounter in general use cash or non-cash media. This task will discuss the payment procedure through the central system. The existence of this central system makes it easier for employees and subsidiaries to make payments. However, the facts on the ground state that many employees and subsidiaries have difficulty using the central system. So that there is a delay in the payment process. Therefore, the practitioner tries to describe the problem and solve the problem based on the SOP that already exists in the company. Analysis of the problem this time using the method of Descriptive Analysis and Fishbone Diagrams. Through the analysis of the production process using Fishbone, it can be concluded that the factor causing this gap is ignorance of employees and company branches regarding payment soup which causes one of the delays in payment. Therefore, the company must make notifications directly to employees and company branches regarding the payment process, so that delays do not occur. In addition, the company can provide training to employees in order to add insight and knowledge to use the centra system.